Business Model Development Logistics for MSME in Rural Areas through Indonesian Postal Infrastructure (PosIND) - Prastyantoro, Riharsono; Gunawan, Andri; Novirani, Dwi (Dinasti Publisher, 2023)
Currently, the potential for logistics business in Indonesia and the world is very large, including the CEP (Courier, Express, Parcel) industry. E-commerce transactions are estimated to grow by 31.2%, resulting in a transaction value of around IDR 526 trillion in 2022. The biggest logistics business opportunities in 2024 are in the food and beverage processing industry, agriculture including the Micro, Small and Medium Enterprises (MSME’s) sector. Online trading gives sufficient contribution? significant in logistics industry in Indonesia. The main MSME’s problem are how make it become digital-based institutions, have source competent staff, sufficient capital as well as get solution efficient logistics. The desired goal achieved from this study is develop concept of rural logistics business for MSME actors based on e-commerce, so can give solution for MSME actors in rural areas as well contribute in reduce logistics national cost. Methodology used? is study library and Focus Group Discussion (FGD). Research goal give contribution theoretical form framework conceptual development logistics business for MSME in rural areas with use CEP operator infrastructure consists of five services business for MSME, namely capital, human resources, marketing and sales, distribution and warehousing or fulfillment. Research goal also provides contribution practically possible implemented by PT Pos Indonesia (PosIND).